DEVELOPING THE MATHEMATICS ENRICHMENT BOOK ON PYTHAGOREAN THEOREM INTEGRATED WITH AUGMENTED REALITY - Pratiwi La Mela, Hartina
Enrichment books are books that contain idea to expand, to deepen, and to complement the main idea in student books. Enrichment books are present as books that can support the students in learning. The used of technology that integrated into enrichment books can increase the motivation in learning. Augmented Reality (AR) is a technology that combines virtual objects and real objects. The used of AR can bring a new atmosphere in learning. The Pythagorean Theorem is a concept that contains the connectedness of the sides of triangles which are widely applied in life. In addition, the Pythagorean Theorem is also a basic concept for mathematics in other aspects. One of which is the concept of Trigonometry. Thus, the concept of the Pythagorean Theorem needs to be well understood. The integration of AR into the Pythagorean Theorem enrichment book can make learning the Pythagorean Theorem more interesting. It is because it can visualize the abstract concepts and present it to the contextual things in real time. The project aims to develop a mathematics enrichment book on the Pythagorean Theorem that integrated with AR. The other goal is to know the effectiveness of the book on learning results on Pythagorean Theorem topic. This book product was developed through the ADDIE development phase. The phase of developing by ADDIE model consist of five phases. It is the analysis phase (Analysis); the design phase (Design); the development phase (Development), the implementation phase (Interpretation), and the evaluation phase (Evaluation). The analysis phase was analyzing the characteristics of the school and students. The design phase was making a draft of the book being developed. The development phase was developing a book based on what has been designed. The implementation phase was testing book to book users. While at the evaluation phase, there was an analysis of the data at the trial stage. At the evaluation phase, improvements were also made to the book which was developed based on the suggestions and criticisms from the trial. The trial of the book product was in two kinds of test. The validty test and the effectiveness test. The validity test was determined by validation from two teachers in Kendari city and two teachers in Bandung city. The effectiveness was determined by giving pre and post tests to students in two different schools. Developers did trials at SMPN 1 Kendari and SMP Kartika Kendari. The number of each student who took the test was 54 and 52 students. The effect of the book was determined by the differences in the average results of the pre-test and post-test. To determine the effect of the book, it was through statistical analysis t-test for paired sample data. Meanwhile, to see the difference in the average of pre and post test, it was through a one-sample t-test. The results of the validation by two teachers in Kendari city showed that books were in the proper category to be used in learning. The same thing came from the validation results by two teachers in Bandung city. Thus, the results of the overall validation showed that the book is in a proper category to be used. The results of the analysis of pre-test and post-test in both schools showed that there was an effect of using books on student learning. The results of the descriptive analysis of the pre-test and post-test showed that the average post-test for each school showed a higher score than the pre-test. The difference in scores of 29.3 and 28.3 respectively. The results of learning after using book for students of SMPN 1 Kendari were students in the high category, while students of SMP Kartika Kendari were in the medium category. Thus, from the results of the validation and testing book, the Pythagorean Theorem Enrichment Book integrated with Augmented Reality is valid to use.